Relationship between inflammatory Response and Pathology of Listeria monocytogenes - Ali Anok Njum1, Jabbar Afate ALwan2, Yasir Faisal Abbas3 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Listeria monocytogenes is a feebly pathogenic, Gram-positive bacterium and ready to develop additionallyat the temperature of 4 C. A man frequently gets influenced by expending tainted water and food. 150 abortedplacentas were achieved from women and cultured directly, while other were fixed in formalin buffer tostudy the effect of CD 45 and CD74 in pathogenesis of Listeria monocytogenes associated with placentitisin aborted women. Results showed six placental samples from out 50 were positive for listeria culture, wereexhibited high expression of CD 45 and CD74 aborted placenta infected with Listeria monocytogenes as acompared to uninfected placenta. This study concluded that a relationship between inflammatory responseand pathology of L. monocytogenes in placental tissue that were collected from aborted women in AlMuthana City